HUBUNGAN ANTARA HIPERTENSI DENGAN PREMENSTRUAL SYNDROME PADA WANITA USIA REPRODUKTIF - Azhim Rahmawati; Retno Siryaningsih; Safari Wahyu Jatmiko (Biomedika, 2014)
Premenstrual syndrome (PMS) is a cycle disorder which is commonly occured during the luteal phase of the menstrual cycle and will dissapear at the time of menstruation. Ninety percent of women on reproductive ages experience symptomps of PMS and 10% of them experience severe premenstrual symptomps that cuse physical disturbance, medical care necessity, even worst death. Hypertension is a risk factor for a PMS. The aim of this research is to find out a conection between PMS and hypertension. This research was designated using analytic observational with cross sectional approach. We used purposive sampling to get sample. Based on sample formula, we got 104 respondents which is consist of 52 women with hypertension and 52 women normotensive. To obtain data, we used shortened premenstrual syndrome assesment form (SPAF). Data collected were analyzed by chi square test. The result showed that the value of p = 0.00 (p0.005). This result indicated that there is a conection between hypertension and PMS occurence in reproductive age. The probability of hypertension women to get PMS is 6.75.Keywords: Hypertension, Premenstrual Syndrome, reproductive age